METHODS FOR DETERMINING THE POSITION OF MOTOR AND TRIGGER POINTS OF THE CHEWING MUSCLES IN DYSFUNCTION OF THE TEMPOROMANDIBULAR JOINT - Kostiuk, T.; Kaniura, A.; Lytovchenko, N. (Проблеми клінічної педіатрії, 2021)
Abstract. Introduction. According to arious publications, from 40 to 60% of the population has various diseases of the temporomandibular joint (TMJ), most of them - functional disorders. A special place in the violation of the temporomandibular joint belongs to the increase in the tone of the masticatory muscles and their dysfunction. The aim of the study. To develop a method for diagnosing the condition of the masticatory muscles in TMJ dysfunction and assess its clinical effectiveness. Materials and methods. During 2018–2019, 35 people with dysfunctional TMJ were under observation. Patients were divided into three groups: I – neuromuscular (20 people), II – occlusal-articulatory (10 people), III – mixed type (5 people). Clinical examination was conducted using a device, designed to provide effective electromyographic examination of the masticatory muscles. Results. It was found that MP AMM on the side of TMJ pathology is shifted upwards compared to MP symmetrical side, with the greatest shift was observed in patients with occlusal-articulatory and mixed pathologies, which indicates prolonged muscle spasm and the need for further rehabilitation. Three weeks after orthopedic and conservative treatment, it was found that the MPs were shifted down and inwards of the AMM relative to the initial one, and after 3 months the MPs on the pathology side were at the same level as the MPs of the symmetrical side.This fact of our observation may indicate muscle relaxation and positive dynamics of intramuscular adjustment. These results of inspection can testify to a long spastic condition of AMM and confirm efficiency of complex treatment of this group of patients. Conclusions. Thus, with the help of the developed diagnostic device not only the initial position of MP and TP muscle was investigated, but also the estimated dynamics of intramuscular adjustment during treatment.